Arbuscular Mycorrhizal Fungi and Dry Raw Garlic Stalk Amendment Alleviate Continuous Monocropping Growth and Photosynthetic Declines in Eggplant by Bolstering Its Antioxidant System and Accumulation of Osmolytes and Secondary Metabolites - Ghani, Muhammad Imran; Ali, Ahmad; Atif, Muhammad Jawaad; Ali, Muhammad; Amin, Bakht; Cheng, Zhihui (Frontiers in Plant Science, 2022)
Vegetable production under plastic shed severely threatens the regional eco-sustainability through anthropogenic activities, excessive use of agrochemicals, pesticides, and persuading replant problems. Long-term continuous cropping spans induced the continuous cropping stress usually manifested in plant growth. Therefore, it is crucial to develop environmentally sustainable approaches like replacing agrochemicals with vegetable waste like dry raw garlic stalk (DRGS) or biofertilizers like Arbuscular mycorrhizal fungi (AMF). In the present study, the influence of AMF (Glomus versiforme L.) on growth, biochemical attributes, antioxidant defense system, phytohormones, accumulation of osmolytes, phenols, and mineral elements in eggplant grown on DRGS amended soils under continuous mono-cropping (CMC) were studied. The results indicate that inoculation of AMF and DRGS amendment increased pigments content, photosynthesis, antioxidant defense system, augmented phytohormones synthesis except for ABA, and increased mineral nutrients. Combined application of AMF and DRGS imparted maximal enhancement of the aforementioned parameters AMF and DRGS increased the concentration of osmolytes, including proline, sugars, and free amino acids, compared to the control. Furthermore, AMF and DRGS alone or in combination ameliorated the continuous cropping induced stress by reducing the incidence of Fusarium wilt and ROS production, lipid peroxidation with the maximal reduction in plants grown under combined treatment. Hence, inoculation of AMF and DRGS amendments alter the photosynthetic attributes in eggplant through the up-regulation of the antioxidant system and the accumulation of osmolytes reflected in improved growth and yield of eggplant.